Measurements and CFD modeling of indoor thoron distribution. (March 2015) - Chauhan, Neetika; Chauhan, R.P.; Joshi, M.; Agarwal, T.K.; Sapra, B.K.
Abstract: Few studies have been undertaken to measure indoor thoron concentration in Indian dwellings. The distribution pattern of thoron inside room conditions is complex due to short half-life. The internal radiation exposure due to inhalation of indoor thoron and decay products can be quite large near to the wall. In this work, Computational Fluid Dynamics (CFD) technique was utilized for prediction of indoor thoron concentration and distribution pattern. Thoron flux was measured experimentally to be used as input and CFD runs were performed for closed and open room conditions. Thoron concentration inside the room was also experimentally measured using Scintillation Thoron Monitor, STM (active) and pin-hole dosimeters (passive). For open room conditions, thoron concentration was found to be smaller and relatively homogenous compared to closed room conditions. CFD predictions were found to be reasonably matching with active and passive results. A separate profile experiment increased confidence towards validation of CFD for indoor thoron distribution (prediction) applications. CFD can be used as a tool to predict thoron concentration and its distribution in indoor conditions. Highlights: Indoor thoron distribution studied out using CFD modeling. Thoron wall flux was measured and used as the key input for modeling. Passive and active measurements were performed to validate the CFD codes. Thoron concentration was found to decay exponentially from wall to center.